The Influence of Different Light Intensity on the Growth of Zoysia matrella Seeds - Utami, Sari Widya; Pratiwi, Artdhita Fajar; Aji, Galih Mustiko (Green Engineering Society, 2024)
Zoysia matrella is a type of highly valued grass, but the seedling time is very long due to the slow growth rate. Several studies have been conducted using artificial light as a light source to accelerate indoor plant production. However, this technology is yet to be widely used for seed production. Therefore, this study aimed to obtain optimal light intensity from artificial light in accelerating Zoysia matrella seedling time. The treatment in the form of Light Emitting Diode (LED) illumination given to increase the growth of Zoysia seedlings consisted of 5 levels, namely 20, 40, 60, 80, and 100 (μmol/m2/s). The parameters studied were germination percentage, germination rate, and vegetative measurement in the form of seedling height in Zoysia nursery chamber equipped with artificial light. The results showed that the artificial illumination technology in the nursery chamber increased the speed of seedling time in the germination and growth phases of Zoysia seeds.